Single-incision Eden-Lange procedure in trapezius muscle paralysis: A report of 11 cases - Morteza Nakhaei Amroodi; Mostafa Salariyeh (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The aim of this study was to evaluate the outcome of single-incision Eden-Lange procedure in trapezius muscle paralysis. Methods: The medical records of 11 patients (3 females and 8 males); mean age: 41 (25–59) years with trapezius muscle paralysis who underwent Eden-Lange procedure in our Center, between February 2009 and April 2013, were retrospectively analyzed. The clinical outcomes were evaluated with the American Shoulder and Elbow Surgeons Shoulder (ASES) score and visual analogue scale (VAS). Results: The mean duration of symptoms before surgery was 10.18 months. The average duration of follow-up was 33.5 (24–48) months. The mean VAS score improved from 7.8 to 1.6 points (p < 0.05). The total ASES improved from 32.8 to 82.1 points (p < 0.05). The mean range of motion in forward elevation and abduction increased significantly from 121.80 to 154.40 (p < 0.05) and 80.00 to 148.18° (p < 0.05), respectively. Conclusion: Single incision Eden-Lange procedure appears to be a safe and effective treatment option for the patients with trapezius muscle paralysis. Level of evidence: Level IV, therapeutic study. Keywords: Trapezius muscle, Paralysis, Eden-Lange procedure, Spinal accessory nerve